The Forgotten View of the Origin of Language: The Legacy of Herder’s Philosophy - Castro, Paulo Alexandre e (Conatus - Journal of Philosophy, 2025)
The question about the origin of language marked modernity with approaches that still echo in contemporary thinkers. This is the case with Herder’s Treatise on the Origin of Language. The question with which Herder opens the essay is significant and expresses well the fundamental problem that marked the philosophical intentions of the 18th century, namely: “Were human beings, left to their natural abilities, able to invent language for themselves?” Forgetting for a moment the implicit reference to God that continued to mark historically the philosophical narratives, it is important to focus the question on the appearance of language. In this sense, the philosopher’s essay is not limited to hypotheses about the emergence of language, or rather, about the founding characteristics of language, but it consolidates it in the anthropological, sociological and even biological horizon from which it allows the understanding of human nature and condition. The enunciation of the four natural laws and the narrative of justification that the philosopher elaborates on reveals a strong potential to understand the phenomenon of language and the human mind. This essay seeks, first, to explain Herder’s theses; second, based on this explanation, see in what sense his approach allows us to understand the phenomenon of the origin and formation of language; and finally, to understand the scope of his work with regard to language and mind, that is, to seek to determine its legacy in contemporary philosophy, namely with regard to the understanding of the human mind. Regarding the latter, it is important to mention two essential points to understand the importance of Herder’s thought for the understanding of the human mind: the mention of reflection as an inner thought and hearing as a fundamental characteristic for the development of language. It is all these questions that this essay seeks to address.